AGENT IN DENNY CAKNAN’S HIT SONGS: JANET WOLFF’S SOCIAL PRODUCTION ANALYSIS - Istikomah, Erna; Wilujeng, Nuning Catur Sri; Endraswara, Suwardi; Widyastuti, Sri Harti (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
This study examines the social ideas embedded in Denny Caknan's hit songs—Kartonyono Medot Janji, Sugeng Dalu, and Los Dol—using Janet Wolff's social production theory. Employing a qualitative descriptive approach, the research integrates intrinsic elements, such as lyrics and music videos, with extrinsic elements, including cultural, social, and personal contexts. The findings reveal that Denny Caknan's works resonate deeply with audiences due to their relatable narratives of heartbreak and resilience, rooted in the Javanese cultural preference for emotionally evocative songs. The "agent" in these works is represented by sobat ambyar (the broken-hearted community), who amplifies the cultural and emotional significance of his music. Additionally, the incorporation of visual elements inspired by modern trends, like Korean dramas, enhances the universal appeal of these songs. This analysis highlights the dynamic interplay between individual creativity and collective cultural production, emphasizing the role of societal influences in shaping artistic expression. Ultimately, Denny Caknan's music exemplifies how popular art can serve as both a reflection of cultural identity and a medium for shared emotional experiences